Income support for the unemployed options for the Philippines - Esguerra, Jude H.; Ogawa, Makoto; Vodopivec, Milan (The Philippine Review of Business and Economics, 2001)
This paper evaluates existing income support programs for the unemployed in the Philippines, as well as programs used for this purpose in other countries. It provides a systematic survey of both arguments in favor of and against a certain program. By placing the discussion in the framework of general risk management, effort is made to adopt a holistic view and treat income support systems for the unemployed in the wider context of other formal and informal mechanisms of social risk management. Particular attention is devoted to the interconnection between unemployment support programs and the financial and, above all, the labor market, the latter being of utmost importance for enhancing the self-protection capacity of individuals and households.